Intrapersonal and Populational Heterogeneity of the Chemokine RANTES - Oran, Paul E. (2010)
BACKGROUND: Current immunoassays for the chemokine RANTES (regulated on activation, normal T-cell expressed and secreted) are not tailored for specific isoforms that exist endogenously, despite the fact that variants with modified activity are known to exist. This is surprising in view of this protein’s ubiquitous increased presence in many diseases and that the 2 established isoforms are truncated by enzymes also correlated to disease. An in-depth population survey of RANTES heterogeneity in the context of multiple diseases via a mass spectrometric immunoassay (MSIA) may resolve this issue. METHODS: We developed an MSIA for RANTES and endogenous variants apparent in human plasma. Samples from multiple cohorts of individuals (type 2 diabetes, congestive heart failure, history of myocardial infarction, and cancer patients) were run in parallel with samples from healthy individuals (239 people total). We used 230 μL of plasma per individual and tabulated relative percent abundance (RPA) values for identified isoforms. RESULTS: We detected at least 19 variants, including the dipeptidyl peptidase IV (DPP-IV)-truncated variant. The majority of variants were unreported in the literature. Identifiable modifications included N- and/or C-terminal truncations, oxidation, glycation, and glycosylation. We observed statistically significant differences in RPA values for multiple variants between disease cohorts and recognized prospective disease-specific protein profiles for RANTES. CONCLUSIONS: Because of widespread interest in the clinical value of RANTES, the protein diversity established here may aid in the design of future, fully quantitative assays. Equally important, an inclusive qualitative understanding of RANTES heterogeneity may present new insights into the relationship between RANTES and disease.